Markers of systemic inflammation in response to osmotic stimulus in healthy volunteers - Sailer, Clara Odilia (Endocr Connect, 2019)
Osmotic stimulus or stress results in vasopressin release. Animal and human in vitro studies have shown that inflammatory parameters, such as interleukin-8 (IL-8) and tumor necrosis factor-α (TNF-α), increase in parallel in the central nervous system and bronchial, corneal or intestinal epithelial cell lines in response to osmotic stimulus. Whether osmotic stimulus directly causes a systemic inflammatory response in humans is unknown. We therefore investigated the influence of osmotic stimulus on circulatory markers of systemic inflammation in healthy volunteers. In this prospective cohort study, 44 healthy volunteers underwent a standardized test protocol with an osmotic stimulus leading into the hyperosmotic/hypernatremic range (serum sodium ≥150 mmol/L) by hypertonic saline infusion. Copeptin – a marker indicating vasopressin activity – serum sodium and osmolality, plasma IL-8 and TNF-α were measured at baseline and directly after osmotic stimulus. Median (range) serum sodium increased from 141 mmol/L (136, 147) to 151 mmol/L (145, 154) (P < 0.01), serum osmolality increased from 295 mmol/L (281, 306) to 315 mmol/L (304, 325) (P < 0.01). Median (range) copeptin increased from 4.3 pg/L (1.1, 21.4) to 28.8 pg/L (19.9, 43.4) (P < 0.01). Median (range) IL-8 levels showed a trend to decrease from 0.79 pg/mL (0.37, 1.6) to 0.7 pg/mL (0.4, 1.9) (P < 0.09) and TNF-α levels decreased from 0.53 pg/mL (0.11, 1.1) to 0.45 pg/mL (0.12, 0.97) (P < 0.036). Contrary to data obtained in vitro, circulating proinflammatory cytokines tend to or decrease in human plasma after osmotic stimulus. In this study, osmotic stimulus does not increase circulating markers of systemic inflammation.